Changes in alternative polyadenylation throughout the yeast metabolic cycle and during glucose starvation in Saccharomyces cerevisiae - Lester, H (2023)
Alternative polyadenylation (APA) is a dynamic and powerful tool to alter gene expression and protein output to rapidly adapt to changes in cellular state. The Yeast Metabolic Cycle (YMC) and a shift from glucose to galactose (the Glu-Gal shift) are two highly metabolically active and dynamic process that are good candidates to explore the role of APA in complex biological systems. Using a combinatorial approach of 3’-RNA-Seq data, in house pipelines to acess APA and gene expression changes and bio-informatics tools to examine similarities and differences, the APA landscape of these processes was profiled and the functions and mechanisms behind its use; explored. The results showed that APA was highly prevalent in both the YMC and Glu-Gal shift and follow distinct temporal profiles. APA events for these processes predominantly occurred at the peaks of metabolic activity. In the YMC, global APA lengthening occurred at the peak of oxygen consumption and during the transition into the R/B phase with the genes involved showing GO enrichment for functional groups related to cell cycle progression and DNA repair. During the Glu-Gal shift, global shortening of mRNA transcripts at genes showing GO enrichment for functional groups related to metabolic processes was observed. There was little overlap of genes that underwent APA events in the YMC and during the Glu-Gal shift, indicating that APA events are mostly specific to a biological process and furthermore, the genes that did go APA in both, showed more generic functions such as response to metabolic stress. In conclusion, APA is a potential regulator to adapt the transcriptome to the metabolic conditions in a cell. Moreover, by examining the context of APA events using Native Elongating Transcript Sequencing (NET-Seq), it become clear that a pas site transition from 3’UTR to the prematurely terminated transcription in the coding region (CR-APA) using transcripts starting at different promoters leads to transcriptional interference and repression of the main transcript. This may represent a novel mechanism to adapt transcriptional output from different promoters to the differing metabolic states in these cells. However, more granular assignment of PAS coupled to techniques such as Transcript IsoForm sequencing (TIFSeq) to assess the integrity of individual transcripts is now required to confirm these observations on the diversity of APA in metabolic adaptations.